(untitled) (Sir Salimullah Medical College Journal, 2023)
Background: Diabetes is one of the most prevalent and serious non-communicable diseases all over the world. It is the leading cause of death, disability and economic loss and thus, it is identified as a major threat to global development. So it is important to evaluate the efficacy and tolerability of drugs in the management of Type 2 DM patients Objective: The purpose of present study was to compare the efficacy and tolerability of gliclazide and metformin in the management of Type 2 DM patients. Methodology: A prospective observational study was conducted in Endocrine outpatient department of Sir Salimullah Medical College & Mitford Hospital and Shaheed Suhrawardy Medical College & Hospital, Dhaka from July 2017- June 2018. A total number of 114 diabetes mellitus patients were taken and divided into two groups. Patient age between 18- 60 years (both male and female) suffering from type 2 diabetes mellitus were included in this study. Patients having the history of Type-1 Diabetes, Hypersensitivity to any drug, pancreatitis , hepatic impairment , high ALT or serum creatinine level (>1.5) , pregnant and nursing woman were excluded from the study. Among the study population one group was given tablet gliclazide and another group was given tablet metformin. Here pre and post baseline investigations( FBG, 2HABF, HbA1c,Serum creatinine , bilirubin, ALT, body height and weight) measured on day 1, follow up at 4 weeks, 12 weeks and then compared. Results: In patients treated with gliclazide mean of pretreatment FBG 8.75±1.79 mmol/ l which was reduced to 6.75±1.19 mmol/l in 4 weeks and 6.26±0.93 mmol/l by 12 weeks. The mean base line serum glucose 2hABF was 13.85±2.52 mmol/l which was reduced to 10.35±2.04 mmol/l in 4 weeks and 9.42±1.59 mmol/l by 12 weeks. In metformin treated group the mean base line FBG was 8.52±2.26 mmol/l which was reduced to 7.01±1.76 mmol/l in 4 weeks and 6.06±0.81 mmol/l by 12 weeks. The mean base line serum glucose 2hABF was 13.23±3.40 mmol/l which was reduced to 10.57±2.19mmol/l at 4 weeks and 9.38±1.71 mmol/l by 12 weeks. Gliclazide and metformin both significantly reduced blood glucose and their efficacy are relatively similar. Adverse effects were seen more in number and intensity with gliclazide. Individual efficacy of both compounds was good but metformin was better tolerated. Conclusion: Metformin is more effective, better tolerated than gliclazide in diabetis mellitus. Sir Salimullah Med Coll J 2023; 31:13-20